2020
DOI: 10.31703/gmcr.2020(v-iv).14
|View full text |Cite
|
Sign up to set email alerts
|

Securitization of Islam and Muslims Through Social Media: A Content Analysis of Stopislam in Twitter

Abstract: The main objective of this paper is to examine the securitization of Islam and Muslims on Twitter. Therefore, whether and to what extent securitized images of Islam and Muslims have been produced on Twitter and to analyze the dominant securitized themes and their sub-dimensions. The methodology used for this purpose consisted of quantitative and qualitative analysis and analyzed hashtags #stopislam trending on Twitter. It was found that #stopislam produced securitized images of Islam and Muslims. Totalitariani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…To ensure validity, the researchers conducted sentiment analysis and applied an instrument of analysis, the technique of data collection by Awan (2016) with some significant modifications, as the primary tool developed by the Online Hate Centre (2013) for the publication of "Islamophobia on the Internet" and adopted by Civila (2020) for Twitter. The study also validates the finding by Khan, Shah, & Ahmad (2020) in analysing Twitter hashtags related to securitisation of Muslims.…”
Section: Operationalisation and Codingsupporting
confidence: 86%
See 3 more Smart Citations
“…To ensure validity, the researchers conducted sentiment analysis and applied an instrument of analysis, the technique of data collection by Awan (2016) with some significant modifications, as the primary tool developed by the Online Hate Centre (2013) for the publication of "Islamophobia on the Internet" and adopted by Civila (2020) for Twitter. The study also validates the finding by Khan, Shah, & Ahmad (2020) in analysing Twitter hashtags related to securitisation of Muslims.…”
Section: Operationalisation and Codingsupporting
confidence: 86%
“…The ideological threat can be studied and understood in four sub-dimensions such as totalitarianism, jihadi, Wahahabism and Sharia law. Similarly, the existential threat aspect is classified as a threat to immigrants, women, refugees and general Muslims (Iqbal, 2019;Khan et al, 2020;Khan, R. A. A et al, 2022).…”
Section: Securitisation Of Islam and Muslimsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Vidgen and Yasseri 2020) describes Islamophobia as a type of racism, stereotyping, prejudice, fear, and dominance. Furthermore, (Ahmed Khan, Shah, and Ahmad 2020) defines Islamophobia as an unfounded fear or hatred of Islam, Islamic values & traditions, and an unjustified hostility towards Muslims. Moreover, they also found that Islamophobia and violence towards the Muslim community has increased in The United States and Europe since 9/11.…”
Section: Introductionmentioning
confidence: 99%